Hubungan antara Antropometri dan Biomotor dengan Keterampilan Menggiring dalam Permainan Sepak Bola - Febri Abdul Faqih; Supriatna Supriatna; Yulingga Nanda Hanief; Roesdiyanto Roesdiyanto (Publikasi Indonesia, 2023)
The relationship between anthropometry and biomotor on dribbling skills has been done in many previous studies. These kinds of studies explain that anthropometric and biomotor relationships have a positive influence, especially on dribbling skills in football athletes. However, the results obtained from each study have different results, so it is necessary to analyze data inclusively and exclusively so that the information provided is valid about anthropometric and biomotor relationships on dribbling skills in football games. The purpose of this study was to find out whether there is a relationship between anthropometry and biomotor with dribbling skills in football games. This research used quantitative research with meta-analysis methods by reviewing several articles in national journals that can be accessed online through google scholar. The findings in this study showed a positive influence on the relationship between anthropometry and biomotor in dribbling skills. With a value of 0.546, which indicates that anthropometric and biomotor relationships in dribbling skills are in the high category. The conclusion of this study is that anthropometric and biomotor relationships in dribbling skills have a significant influence on soccer games, especially on dribbling skills.